Algorithms for Analysis of Television and Thermal Images in Special-purpose Video Devices and Systems - Boyun, V.P.; Sabelnikov, P.Yu.; Sabelnikov, Yu.A. (Science and Innovation, 2024)
The results of the research project «Development of algorithms and program models for the analysis of television and thermal images» (code VC 200.16.13) have been presented. The existing methods and algorithms for processing the television and thermal video images have been analyzed and the new techniques that will allow the researchers to create more effective video devices and systems for special purposes have been offered.